2022
DOI: 10.1080/19490976.2022.2070391
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Escherichia coli Nissle 1917 with urate oxidase and an oxygen-recycling system for hyperuricemia treatment

Abstract: Hyperuricemia is the second most prevalent metabolic disease to human health after diabetes. Only a few clinical drugs are available, and most of them have serious side effects. The human body does not have urate oxidase, and uric acid is secreted via the kidney or the intestine. Reduction through kidney secretion is often the cause of hyperuricemia. We hypothesized that the intestine secretion could be enhanced when a recombinant urate-degrading bacterium was introduced into the gut. We engineered an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 83 publications
(86 reference statements)
1
12
0
Order By: Relevance
“…Compared with the CON group, the composition of gut microbiota at the phylum level showed that the relative abundance of Firmicutes was significantly decreased, whereas Bacteroidetes and Proteobacteria were markedly increased in the MOD group ( Figure 8F ). This imbalance of gut microbiota was recovered in the Q7 group, and the corresponding symptoms of HUA were further relieved, which was consistent with the reports of Zhao et al ( 32 ). The difference of gut microbiota in each group at the genus level suggested that the relative abundance of Muribaculaceae was increased after HUA modeling, the relative abundance of Lachnospiraceae _NK4A136_group, Prevotellaceae _UCG-001 and Prevotellaceae _NK3B31_group were decreased, while those flora in the Q7 group were recovered to the level of CON group ( Figure 8G ).…”
Section: Resultssupporting
confidence: 91%
“…Compared with the CON group, the composition of gut microbiota at the phylum level showed that the relative abundance of Firmicutes was significantly decreased, whereas Bacteroidetes and Proteobacteria were markedly increased in the MOD group ( Figure 8F ). This imbalance of gut microbiota was recovered in the Q7 group, and the corresponding symptoms of HUA were further relieved, which was consistent with the reports of Zhao et al ( 32 ). The difference of gut microbiota in each group at the genus level suggested that the relative abundance of Muribaculaceae was increased after HUA modeling, the relative abundance of Lachnospiraceae _NK4A136_group, Prevotellaceae _UCG-001 and Prevotellaceae _NK3B31_group were decreased, while those flora in the Q7 group were recovered to the level of CON group ( Figure 8G ).…”
Section: Resultssupporting
confidence: 91%
“…In addition, there are 10 nucleobase‐ascorbate transporter (NAT) family‐related proteins in E. coli that are responsible for transporting different forms of base metabolites. Further, the ygfU gene located at the inner membrane was hypothesized to import urate 61 and overexpression of YgfU could improve the urate degradation efficiency in E. coli 62 . However, our data showed that cytoplasmic expression of uricase in the EcN strain only slightly decreased the urate level in vitro (Figure S1b), suggesting that the efficiency of urate import may be limited by the bacterial cell membrane or the affinity of urate transporters.…”
Section: Discussionmentioning
confidence: 76%
“…Traditional probiotics can be easily engineered and are the chassis of choice. For example, engineered EcN has been developed into various biopharmaceuticals, − and its genomic, transcriptomic, and metabolic properties have been intensively studied . In fact, lactic acid bacteria now support various CRISPR/Cas systems − and have long been developed as mature heterologous production platforms, biocontrol systems, and biosensors .…”
Section: Chassismentioning
confidence: 99%
“…For instance, recombinant L. lactis heterologously expressing IL-10 has been used to treat DSS-induced model mice in situ since 2000 . This effective and simple method was immediately extended to different probiotic chassis and applied to different treatment scenarios, ,, resulting in numerous practical research findings. For example, the engineered probiotic SYNB1618, developed by Synlogic to treat phenylketonuria, has successfully completed phase II trials, and represents a milestone for living therapeutics. , …”
Section: Design Of Functional Gene Circuitsmentioning
confidence: 99%
See 1 more Smart Citation